1983
DOI: 10.1083/jcb.97.2.329
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-mediated endocytosis of transferrin and recycling of the transferrin receptor in rat reticulocytes.

Abstract: At 4°C transferrin bound to receptors on the reticulocyte plasma membrane, and at 37°C receptor-mediated endocytosis of transferrin occurred. Uptake at 37°C exceeded binding at 4°C by 2.5-fold and saturated after 20-30 min. During uptake at 37°C, bound transferrin was internalized into a trypsin-resistant space. Trypsinization at 4°C destroyed surface receptors, but with subsequent incubation at 37°C, surface receptors rapidly appeared (albeit in reduced numbers), and uptake occurred at a decreased level. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
1,033
4
17

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,525 publications
(1,139 citation statements)
references
References 42 publications
21
1,033
4
17
Order By: Relevance
“…Most likely, overexpression of PACSIN3 causes an inhibition of GLUT1 endocytosis, and thereby causes the increase in the plasma membrane. Previously, PACSIN3 overexpression has been shown to inhibit transferrin uptake, which proceeds via the transferrin receptor by the clathrin-coated pit pathway of endocytosis [11,20]. In agreement with this finding, we found that PACSIN3 overexpression caused an increase in transferrin receptor in the plasma membrane.…”
Section: Discussionsupporting
confidence: 91%
“…Most likely, overexpression of PACSIN3 causes an inhibition of GLUT1 endocytosis, and thereby causes the increase in the plasma membrane. Previously, PACSIN3 overexpression has been shown to inhibit transferrin uptake, which proceeds via the transferrin receptor by the clathrin-coated pit pathway of endocytosis [11,20]. In agreement with this finding, we found that PACSIN3 overexpression caused an increase in transferrin receptor in the plasma membrane.…”
Section: Discussionsupporting
confidence: 91%
“…EVs were described by two independent studies, in 1983 [11] and 1984 [12], when it was observed that reticulocytes could discharge the transferrin receptor by its incorporation into EVs that were then released by cells. These vesicles were termed exosomes as they originated from the endosome/multivesicular bodies [13].…”
Section: Extracellular Vesicles/exosomesmentioning
confidence: 99%
“…Furthermore, as unique markers for the different vesicle types have not yet been fully defined, the origin of vesicles released from cells cannot be identified. For this reason, here we use the collective term EVs [10][11][12][13][14].…”
Section: Extracellular Vesicles/exosomesmentioning
confidence: 99%
“…During exocytosis, in addition to soluble proteins and mediators, vesicles heterogeneous in size and shape, termed exosomes, are released from the lumen of multivesicular bodies in the extracellular environment (3,4).…”
Section: Mast Cell-derived Exosomes Induce Phenotypic and Functionalmentioning
confidence: 99%